2016
DOI: 10.1105/tpc.16.00018
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Structure of the GRAS Domain of SCARECROW-LIKE7 inOryza sativa

Abstract: GRAS proteins belong to a plant-specific protein family with many members and play essential roles in plant growth and development, functioning primarily in transcriptional regulation. Proteins in the family are minimally defined as containing the conserved GRAS domain. Here, we determined the structure of the GRAS domain of Os-SCL7 from rice (Oryza sativa) to 1.82 Å. The structure includes cap and core subdomains and elucidates the features of the conserved GRAS LRI, VHIID, LRII, PFYRE, and SAW motifs. The st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
62
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(70 citation statements)
references
References 51 publications
(50 reference statements)
1
62
0
2
Order By: Relevance
“…Our study revealed that the GRAS domains of SHR and SCR each comprise an α-helical cap and α/β core subdomains, which is similar to the recently reported structure of SCARECROWLIKE7 in rice (OsSCL7) (Supplementary Fig. 11) 30 . In general, the GRAS domain shows structural similarity with SAM-MT α/β enzymes.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Our study revealed that the GRAS domains of SHR and SCR each comprise an α-helical cap and α/β core subdomains, which is similar to the recently reported structure of SCARECROWLIKE7 in rice (OsSCL7) (Supplementary Fig. 11) 30 . In general, the GRAS domain shows structural similarity with SAM-MT α/β enzymes.…”
Section: Discussionsupporting
confidence: 88%
“…12). In addition, OsSCL7 forms a homodimer 30 . These findings suggest that there are subtypes of GRAS proteins with different physical properties as determined by the α-helical caps, which mediate hetero- and/or homo-dimerization, or the absence of dimerization altogether.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Whereas their N-terminal regions vary, members of this family are characterized by a C-terminal region harboring the GRAS domain. In a landmark article, Li et al (2016) report the crystal structure of the GRAS domain, thereby providing long-awaited insight into potential mechanisms underlying the widespread importance of GRAS domain proteins.…”
mentioning
confidence: 99%
“…The five subdomains of the Os-SCL7 GRAS domain are colored according to the schematic below the structure (adapted from Figure 1 of Li et al [2016] …”
mentioning
confidence: 99%